2015
DOI: 10.1063/1.4906754
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-dependent magnetism and orbital structure of strained YTiO3 films on LaAlO3 substrates

Abstract: The strain tuned magnetism of YTiO 3 film grown on the LaAlO 3 (110) substrate is studied by the method of the first principles, and compared with that of the (001)-oriented one. The obtained magnetism is totally different, which is ferromagnetic for the film on the (110) substrate but A-type antiferromagnetic on the (001) one. This orientation-dependent magnetism is attributed to the subtle orbital ordering of YTiO 3 film. The d xz /d yz -type orbital ordering is predominant for the (001) one, but for the (11… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Even for a single material film, the growth orientation may alter the ground state. In a recent study, we found that the YTiO 3 film on LaAlO 3 becomes A-type antiferromagnetic when growing along the [001]-axis [12], while it retains ferromagnetism when growing along the [110]axis; this finding agrees with experimental observations [13,14]. For LaTiO 3 , the exchange coefficients and, thus, the Neel temperature were predicted to be significantly enhanced in the [111] bilayer compared with the [001] one [15].…”
Section: Introductionsupporting
confidence: 86%
“…Even for a single material film, the growth orientation may alter the ground state. In a recent study, we found that the YTiO 3 film on LaAlO 3 becomes A-type antiferromagnetic when growing along the [001]-axis [12], while it retains ferromagnetism when growing along the [110]axis; this finding agrees with experimental observations [13,14]. For LaTiO 3 , the exchange coefficients and, thus, the Neel temperature were predicted to be significantly enhanced in the [111] bilayer compared with the [001] one [15].…”
Section: Introductionsupporting
confidence: 86%
“…7,28 Previous theoretical work has also explored strain as a possible strategy for stabilizing the A-AFM phase in rare-earth titanates (and specifically GdTiO 3 ) although much larger values of strain were typically required. [29][30][31][32] Figure 6(a) now shows that excitation of the same IR-active phonon (now at 70.8 meV in the strained material) pushes GdTiO 3 across the phase boundary, stabilizing the A-AFM phase at lower peak electric fields than in the unstrained system. We find that the combined peak IR and Raman response stabilizes the A-AFM phase for E 0 > 2.5 MV/cm.…”
Section: Magnetic Phase Transition In Gdtiomentioning
confidence: 94%
“…For example, LTO and YTO films grown on the compressive [001] LaAlO 3 (LAO) substrate were predicted to show A-type antiferromagnetism (AFM) although their bulks show different original magnetic orders [13,14]. In addition to the substrate constraint (e.g., compressive or tensile), the growth orientation is also important in determining the physical properties of oxide films and superlattices, such as orientation-dependent magnetism and orientationdependent metal-insulator transition [15][16][17][18][19][20].…”
mentioning
confidence: 99%